PERAN PEMERINTAH DAERAH DALAM RANGKA PENGEMBANGAN EKONOMI KREATIF PADA SEKTOR KERAJINAN DI KABUPATEN BATU BARA (STUDI KASUS KERAJINAN TENUN SONGKET DI KECAMATAN TALAWI KABUPATEN BATU BARA) - Putri Kesuma Wardani (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
This study aims to find out what are the obstaces and the roe (efforts) of the oca government in deveoping the creative economy in the handicraft sector in Batu Bara Regency. The oca government as the panner's roe is to design and form interactions in a process towards the goas to be achieved, one of which is the deveopment of the creative economy in the craft sector, especially in the Coal Songket Weaving craft. Creative Economy (Creative Industry) is a new economic concept that relies on ideas, ideas, or creativity from human resources as the main production factor in economic activity. Songket woven fabric is one of the cultural products of the community and is a superior craft product in Batu Bara Regency. This research method uses a quaitative approach with data collection techniques, namely primary data by interviewing informants consisting of Regiona Apparatus Organizations, Historian, and Coa Songket Weaving Craftsmen. Whieh secondary data is obtained by citing sources from the Qur'an, several government documents, books, journals, other written media and websites. The results of this study indicate that in the context of developing the creative economy in the craft sector in Batu Bara Regency, especially in the Coa Songket Weaving craft, the government is experiencing obstacles, namely because of the high price of songket so that it has an impact on its marketing, there are human resources who are less trained to be more creative and creative. innovative. On the other hand, the local government is directly invoved in the deveopment of handicrafts in Batu Bara Regency. oca governments have roles as facilitators, coordinators, and assist in marketing through promotions.